المركز القانوني للأفريبول بين أشخاص القانون الدولي العام - الملود, نعيم; حميدة, نادية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2021)
تهدف هذه الدراسة إلى تسليط الضوء على الأفريبول بإعتباره الآلية الإفريقية للتعاون الشرطي و الذي يقع مقره في الجزائر، ومعرفة مدى اكتسابه للعناصر الواجب تحققها للتمتع بالشخصية القانونية الدولية، والتي يتحدد بموجبها مركزه القانوني بين أشخاص القانون الدولي العام، خاصة وأنه يظهر تارة تابع فنيا للمنظمة الدولية للشرطة الجنائية أنتربول بحكم تداخل تخصصهما الفني المشترك، و تارة أخرى يظهر كجهاز تابع هيكليا للإتحاد الإفريقي بالنظر لعنصر العضوية الموحد بينهما، و للإجابة على هذه الإشكالية تم الإعتماد على المنهج الوصفي التحليلي وبالإستناد على الإتفاقيات الدولية التي تحكم الأفريبول؛ لتخرج الدراسة في الأخير بإستنتاج أن الأفريبول هو منظمة دولية إقليمية متخصصة شأنه شأن الوكالات الدولية المتخصصة التابعة لمنظمة الأمم المتحدة. Abstract: This study aims to shed light on the AfriPol, which is based in Algeria, as the African mechanism for police cooperation and knowledge of its legal status among persons of public international law, especially as it appears at times a technical affiliate of the International Criminal Police Organization Interpol by virtue of their common specialization, and at other times it appears as a subsidiary Structurally for the African Union in view of the membership component, and to answer this problem, the analytical and descriptive approach was relied upon and based on the international agreements that govern AfriPol, so the study finally comes out with the conclusion that AfriPol is a specialized international regional organization as an international specialized agencies of the United Nations